Evidence of disturbed sleep and increased illness in overreached endurance athletes - Hausswirth, C.; Louis, J.; Aubry, A.; Bonnet, G.; Duffield, R.; Le Meur, Y. (Medicine & Science in Sports & Exercise, 2014)
Purpose: This study aimed to examine whether (i) objective markers of sleep quantity and quality are altered in endurance athletes experiencing overreaching in response to an overload training program and (ii) potential reduced sleep quality would be accompanied with a higher prevalence of upper respiratory tract infections in this population.